Organo-mineral interactions modulate organic carbon retention and mobility in a deep subterranean estuary of a high-energy beach - Amoako, Kojo; Reckhardt, Anja; Roberts, Magali; Meyer, Rena; Brick, Simone; Dittmar, Thorsten; Waska, Hannelore (Frontiers in Water, 2025)
Permeable sandy sediments beneath high-energy beaches act as potent biogeochemical reactors with high organic matter turnover rates. Despite their significant role in nutrient and Fe cycling in coastal environments, their capacity to trap and mobilize dissolved organic matter (DOM) remains poorly understood. This study analyzed the molecular composition of water- and acid-leachable sedimentary organic matter down to 24 meters depth in an exemplary subterranean estuary (STE) site of a high-energy beach on Spiekeroog Island, German North Sea. We also investigated DOM coprecipitation with Fe3+ (oxy)hydroxides in the aqueous phase in STE porewaters containing reduced Fe2+, exposed to atmospheric oxygen. We employed fluorescence spectroscopy and ultrahigh-resolution mass spectrometry for our molecular analysis. Seawater and STE porewater DOM were more complex and oxidized than DOM leached from the sediments. Sediment leaching with ultrapure water predominantly yielded aliphatic, oxygen-rich, and presumably labile compounds of marine and possibly autochthonous origin. In contrast, DOM in subsequent 0.5 M hydrochloric acid (HCl) leachates was more molecularly diverse, enriched with oxidized aromatic compounds likely terrigenous and refractory in nature. Notably, acid leachates also contained a substantial fraction of labile compounds. Approximately 10% of total organic carbon (TOC) was leachable as dissolved organic carbon (DOC) in both water and acid treatments. Leachable DOC concentrations were up to two orders of magnitude higher than porewater DOC, while TOC was up to three orders of magnitude higher. These findings indicate that deep sediments are important organic matter reservoirs. Elevated leachable DOC and Fe concentrations in acid treatments were associated with finer, likely clay-rich sediments, while lower levels coincided with coarser sediments. This suggests that Fe oxides/hydroxides act as adsorption sites for terrigenous DOM within the mineral matrix of STE sediments. While Fe-DOM coprecipitation of aerated porewater samples induced distinct molecular alterations, DOC removal was within analytical uncertainties, and molecular fractionation varied across sampling campaigns. Thus, Fe-DOM coprecipitation in the aqueous phases at redox interfaces in the deep (>5 m) STEs appears limited and influenced by transport-driven geochemical changes. We propose that Fe-rich minerals and clay fractions in deep STE sediments facilitate the preservation of refractory, terrigenous DOM, whereas loosely bound, labile DOM fractions—susceptible to rapid microbial respiration—may be readily mobilized by advective water flow in high-energy STEs.